Using Telemedicine Strategy to Implementing Nutrition Management for Neonates After Congenital Heart Disease Surgery: A New Nutrition Management Strategy - Zhang, Qi-Liang; Lin, Wen-Hao; Lin, Shi-Hao; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2022)
Objective The purpose of this study was to investigate the effect of remote nutrition management on promoting the growth and development of neonates after congenital heart disease (CHD) surgery. Materials and Methods This study retrospectively analyzed the clinical data of 32 neonates after CHD surgery who received remote nutrition management from January 2021 to July 2021 in our hospital. The clinical data of 30 neonates after CHD surgery, who did not receive remote nutrition management from June 2020 to December 2020, was used as control. The growth and development of the two groups were compared. Results Three months after discharge, the weight, height, and weight-for-age z score (WAZ) of the intervention group was significantly higher than those of the control group. The amount of milk in the intervention group was also significantly more than that of the control group, and more neonates in the intervention group added high-energy milk or breast milk fortifier than the intervention group. The parental care ability of the intervention group was significantly higher than that of the control group. The incidence of respiratory tract infection and readmission in the intervention group was significantly lower than that in the control group. Conclusion As a new nutrition management strategy for neonates after CHD surgery, remote nutrition management can effectively improve the nutritional status of neonates and promote their growth and development.